Drivers of Praise and Complaint in TripAdvisor Reviews from Guest Stay Experiences (Pusat Riset dan Inovasi Nasional, 2026)
Online reviews on platforms such as TripAdvisor have become a determinant factor in tourists' hotel selection decisions. This study aims to identify and compare the driving factors of positive and negative reviews on TripAdvisor from the perspective of hotel guests' stay experiences in Semarang City. A qualitative approach using thematic analysis method was applied to 127 reviews consisting of 64 positive reviews (rating 4–5) and 63 negative reviews (rating 1–2) from 15 star-rated hotels. The findings reveal five main themes driving positive reviews: staff service quality (90.6%), cleanliness and comfort (81.3%), perceived value (64.1%), strategic location (59.4%), and culinary experience (53.1%). Meanwhile, negative reviews were driven by facility failures (81.0%), expectation discrepancy (74.6%), cleanliness deficiency (69.8%), poor service quality (61.9%), and noise issues (44.4%). Comparative analysis identified convergent patterns in staff service, cleanliness, facilities, and expectations dimensions that function as drivers for both types of reviews. Divergent patterns were found in location and culinary aspects that exclusively appeared in positive reviews, and noise issues that only emerged in negative reviews. These findings confirm the expectancy-disconfirmation theory and provide practical implications for hotel management to prioritize staff competency development, preventive facility maintenance, and accurate expectation management.